Effect of Eggshell Waste Filler Content on Impact Strength and Physical Properties of Jute Fiber Reinforced Recycled HDPE Composites - Ikhsan Eka Pramudya; Kriswanto; Kaleb Kaleb Priyanto; Muhammad Eka Rizky Ramadhan (Universitas Medan Area, 2026)
This study investigates the influence of eggshell waste-derived calcium carbonate (CaCO₃) filler content on the impact strength and density characteristics of jute fiber reinforced recycled high-density polyethylene (r-HDPE) composites. The research addresses the dual challenge of plastic waste management and agricultural waste utilization by developing sustainable composite materials suitable for automotive applications. Eggshell waste was mechanically processed to produce CaCO₃ filler particles passing through 300-mesh screens, while r-HDPE was sized to pass through 50-mesh screens. Jute fibers in plain weave configuration were subjected to alkaline treatment using 5% NaOH solution to enhance fiber-matrix adhesion. Composite specimens were fabricated using compression molding technique with CaCO₃ filler content varied systematically at 0%, 2%, 4%, 6%, and 8% by volume fraction. Impact testing was conducted according to ISO 179 standards using Charpy impact testing, while density measurements followed ASTM D 792 procedures. Macroscopic failure analysis was performed through stereomicroscopic examination of fracture surfaces. The results revealed complex relationships between filler content and mechanical performance. The addition of 2% CaCO₃ produced marginal impact strength improvement of 0.5%, while higher filler loadings of 4%, 6%, and 8% resulted in progressive deterioration of 1.1%, 1.8%, and 1.9% respectively compared to the baseline composite. Density measurements showed systematic increases of 5.1%, 13.2%, 16.3%, and 23.2% for 2%, 4%, 6%, and 8% CaCO₃ content respectively, confirming successful filler incorporation. Macroscopic failure analysis revealed a transition from ductile to brittle fracture behavior with increasing filler content, characterized by reduced fiber pull-out lengths and cleaner fracture surfaces. The findings indicate that while eggshell-derived CaCO₃ offers environmental benefits through waste utilization, optimal mechanical performance requires careful control of filler content and surface modification strategies to achieve effective particle-matrix compatibility in sustainable composite systems